Symptom Distress Associated with Biopsy in Women with Suspect Breast Lesions. (8th July 2012) - Kamath, Jayesh; Cruess, Dean G.; Claffey, Kevin; Wilson, Lori; Phoenix, Natalie; Tannenbaum, Susan
Abstract : Purpose . To investigate symptom distress, quality of life, affective states, and inflammatory biomarkers before and after breast biopsy in women undergoing breast biopsy. Methods . A convenience sample of 47 women undergoing breast biopsy was assessed at the pre- and post-biopsy visits. The assessments included evaluation of fatigue, anxiety, depression, sleep disturbances, positive and negative affect, quality of life using validated self report measures, and a blood draw to determine markers of inflammation. Results . At the postbiopsy visit, a total of 15 participants were diagnosed with breast cancer, and 32 participants received negative biopsy result. The mean anxiety and sleep disturbances scores were in the clinically significant range for the total sample and for the biopsy positive (BC+) and biopsy negative (BC−) subgroups at both time points. For both subgroups, anxiety and sleep disturbances scores did not change significantly from pre- to post-biopsy. A subpopulation of participants in both groups reported moderate-to-severe anxiety, depression and fatigue levels at both time points. The inflammatory markers did not show consistent associations with psychosocial symptoms. Conclusions . A subset of participants in BC+ and BC− subgroups experience heightened symptom distress and negative impact on quality of life at both pre- and post-biopsy time points.